2008
DOI: 10.4049/jimmunol.181.9.5842
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IFN-γ Enables APC to Promote Memory Th17 and Abate Th1 Cell Development

Abstract: Th1-derived IFN-γ targets naive T cells and inhibits Th17 development. However, Th1, Th17, and memory but not naive T cells are colocalized in an inflammatory environment. To demonstrate the kinetic relationship between these T cell subsets, we investigated the role of IFN-γ in regulating the development and balance between Th17 and Th1 in humans. We show that IFN-γ stimulates B7-H1 expression on APC subsets and abates their Th1 polarization capacity in a B7-H1-dependent manner. Interestingly, IFN-γ triggers A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 31 publications
(52 reference statements)
5
77
0
Order By: Relevance
“…Macrophages outnumbered myeloid DCs in ovarian cancer 19,21 (supplemental Figure 3) and were superior to inducing Th17 cells than myeloid DCs (supplemental Figure 4, Figure 3B). 29 Our subsequent studies focused on tumor-associated macrophages.…”
Section: Induction and Suppression Of Th17 Cell Development In The Tumentioning
confidence: 99%
“…Macrophages outnumbered myeloid DCs in ovarian cancer 19,21 (supplemental Figure 3) and were superior to inducing Th17 cells than myeloid DCs (supplemental Figure 4, Figure 3B). 29 Our subsequent studies focused on tumor-associated macrophages.…”
Section: Induction and Suppression Of Th17 Cell Development In The Tumentioning
confidence: 99%
“…6,7 Th17-lineage CD4 ϩ T cells, which express the transcription factor ROR-␥t and produce the proinflammatory cytokine interleukin-17 (IL-17), demonstrate enhanced antitumor immunity. 8,9 IL-17-producing CD8 ϩ T cells have been identified in mice and in humans, [10][11][12][13] and they can be generated through in vitro priming with Th17-polarizing cytokines. 14 However, a role for these cells in antitumor immunity has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancers arise from the sites of infection, chronic irritation and inflammation as shown in Table 1, the inflammatory conditions are present before a malignant change occurs. To understand the kinetics and targets of inflammation in a discussion of T H 17 cells and cancer, the relationship between T H 1-derived IFN, T H 17 cells and antigen-presenting cells (APCs) in humans was recently studied (Kryczek et al, 2008a). These authors demonstrated in a cutting edge study that IFN could rapidly induce elevated B7-H1 expression on APCs and stimulate their production of IL-1 and IL-23.…”
Section: Association Of T H 17 Cells With Chronic Inflammationmentioning
confidence: 98%